The 2019 World Science Forum, 20–23 November in Budapest, Hungary - Editors (New Zealand Science Review, 2019)
The 2019 World Science Forum, which takes place in Budapest, Hungary, between the 20 and 23 of November, will provide an opportunity for the considerations of scientists, policy-makers, society, industry and science communicators to be challenged from an ethical standpoint in the plenary sessions, and will also allow for more technical debates over issues of science in thematic sessions. The first UNESCO World Conference on Science was held in 1999 in Budapest. Since 2003 the Forum has played a prominent role in bringing leaders of the world of science and policy together. The biennial Forum aims to discuss the roles, responsibilities and challenges of science and present issues of common interest to the scientific community and the general public. Partner organisations of the World Science Forum are the: United Nations Educational Scientific and Cultural Organisation (UNESCO); International Science Council (ISC); American Association for the Advancement of Science; the InterAcademy Partnership (IAP); World Academy of Sciences (TWAS); European Academies Science Advisory Council (EASAC); and Hungarian Academy of Sciences as the initiator of the host of the 2019 Forum.